Efektifitas Pembelajaran Bahasa Arab dengan Wordwall Untuk Meningkatkan Antusiasme dan Pemahaman Siswa MA Al-Bairuny - Dian Kusuma Wardani; Aufia Aisa; Maysarotud Dinul Qoyyimah; Umi Unzilatur Rohmah; Maulida Eva Maisaroh (El-Syaker : Samarinda International Journal of Language Studies, 2025)
Learning Arabic as a foreign language presents challenges due to its complex grammar, vocabulary, and speaking skills, often leading to low student motivation. Traditional teaching methods may not sufficiently engage students, which calls for innovative approaches to enhance learning. One such method is the use of Wordwall, a digital platform offering interactive educational games. This study aims to assess the effectiveness of Wordwall in increasing students' enthusiasm and understanding of Arabic at MA Al-Bairuny. Using a classroom action research design, the research includes stages of planning, implementation, observation, and reflection. Data was collected through pretests, posttests, observations, and questionnaires. The pretest and posttest were used to measure improvements in student understanding, while observations and questionnaires assessed their engagement. The results indicate that Wordwall significantly improved student learning outcomes, with 100% of students completing the posttest successfully, showing a marked improvement over the pretest. Additionally, most students reported that learning with Wordwall was more engaging and helped them understand the material better. Observations further revealed that students were more active in class compared to traditional methods. In conclusion, Wordwall is an effective tool for enhancing student motivation and understanding in Arabic learning. It is recommended as an innovative teaching strategy for educators, and future research should explore its impact on improving speaking and writing skills in Arabic.